Soliton solution of the coupled nonlinear Klein Gordon equations with two integration schemes - Ja'afar Mohamad Jawad, Anwar (International Journal of Engineering and Technology, 2019)
This paper established a traveling wave solution by using Sech - Csch function algorithms as well as the Modified Simple Equation Method (MSEM) for nonlinear partial differential equations. These methods will be applied to solving the conservation laws of the coupled Klein-Gordon equations that arise in the quantum field theory. There are two types of nonlinearity that will be considered, namely the cubic and the power law. The conservation laws will be finally determined from these conserved densities from the corresponding soliton solution.Â